2012
DOI: 10.1590/s0100-736x2012000700012
|View full text |Cite
|
Sign up to set email alerts
|

Canine papillomatosis: a retrospective study of 24 cases (2001-2011) and immunohistochemical characterization

Abstract: A retrospective study of 24 cases of papillomas in dogs was performed from January 2001 to March 2011. Additionally, immunohistochemistry (IHC) was used to characterize and evaluate the samples. We found that disease was observed more in mixed breed dogs, ages ranging from 6 months to 10 years (mean 3.1 years), and there was no gender predilection. The main lesion sites were the skin (75%), lips (16.7%), and eyelids (8.3%). Upon histological evaluation, we observed papillary exophytic proliferation of squamous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…39,[65][66][67][68] Table 3 summarizes different diagnostic tests used to confirm infections of CPV. 2,5,8,22,[28][29][30][31]36,37,39,64,66,68,69,70,71 Veterinarians must be aware that CPV has the potential to induce latent infections. One study demonstrated CPV DNA in 23% of oral samples collected from healthy dogs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…39,[65][66][67][68] Table 3 summarizes different diagnostic tests used to confirm infections of CPV. 2,5,8,22,[28][29][30][31]36,37,39,64,66,68,69,70,71 Veterinarians must be aware that CPV has the potential to induce latent infections. One study demonstrated CPV DNA in 23% of oral samples collected from healthy dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Koilocyte and inclusion bodies. 36,39,64 Histopathology is the most common test for diagnostic canine oral papillomavirus (COVP) infections. 28 Evaluation of lymphocytic infiltration is possible by this method, facilitating the differentiation between regressive and nonregressive lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Koilocytosis is commonly identified histopathological analyses of papillomas in different organisms, including canines (Bianchi et al, 2012) and humans (Betiol et al, 2012;Rogovskyy et al, 2012). Koilocytes are degenerated keratinocytes that are destined for cell death or epithelium release.…”
Section: Molecular Diagnosis and Histopathological And Immunohistochementioning
confidence: 99%
“…The Papillomavirus is a DNA virus that has special affinity towards the cutaneous squamous or mucosal epithelium (Gross et al, 2008). Canine papillomatosis is commonly seen in mixed-breed dogs of age in between 6 months to 10 years, and majority of the lesions are seen in skin followed by lips (Bianchi et al, 2012). Studies conducted by Sundberg et al, 1994 have reported that dogs with immunosuppressive disorders are highly predisposed to canine papillomatosis.…”
Section: Introductionmentioning
confidence: 99%